Sensor measures of symmetry quantify upper limb movement in the natural environment across the lifespan. - Smith, Beth A. (Arch Phys Med Rehabil, 2019)
Knowledge of upper limb activity in the natural environment is critical for evaluating the effectiveness of rehabilitation services. Wearable sensors allow efficient collection of these data, and have the potential to be less burdensome than self-report measures of activity. Sensors can capture many different variables of activity and daily performance, many of which could be useful in identifying deviation from typical movement behavior and/or measuring outcomes from rehabilitation interventions. While it has potential, sensor measurement is just emerging and there is a lack of consensus on which variables of daily performance are valid, sensitive, specific, and useful. We propose that symmetry of full-day upper limb movement is a key variable. We describe here that symmetry is valid, robustly observed within a narrow range across the lifespan in typical development, and shows evidence of being different in populations with neuromotor impairment. Key next steps include the determination of sensitivity, specificity, minimal detectable change, and minimal clinically important change/difference. This information is needed to determine whether an individual belongs to the typical or atypical group, whether or not change has occurred, and whether or not that change is beneficial.